2020
DOI: 10.1016/j.chest.2020.04.061
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Characteristics and Progression of a Spectrum of Interstitial Lung Abnormalities and Disease in Rheumatoid Arthritis

Abstract: BACKGROUND: Interstitial lung abnormalities (ILA) and interstitial lung disease (ILD) are seen in up to 60% of individuals with rheumatoid arthritis (RA), some of which will progress to have a significant impact on morbidity and mortality rates. Better characterization of progressive interstitial changes and identification of risk factors that are associated with progression may enable earlier intervention and improved outcomes. RESEARCH QUESTION: What are baseline characteristics associated with RA-ILD progre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
24
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 38 publications
(56 reference statements)
6
24
0
2
Order By: Relevance
“…The identification of progressive ILA may enable appropriate surveillance and the commencement of treatment with the goal of improving morbidity and mortality rates of established RA-ILD. Kawano-Dourado L et al [ 35 ] performed a longitudinal study in order to characterize risk factors associated with progression in RA-ILA and RA-ILD patients. Of 293 individuals with RA and clinically indicated CT studies, interstitial changes were observed in 22 % (64 of 293; older male smokers), one half of whom had a respiratory complaint at the time of imaging.…”
Section: Implication Of Ila In Ctd: Radiologic Perspectivementioning
confidence: 99%
“…The identification of progressive ILA may enable appropriate surveillance and the commencement of treatment with the goal of improving morbidity and mortality rates of established RA-ILD. Kawano-Dourado L et al [ 35 ] performed a longitudinal study in order to characterize risk factors associated with progression in RA-ILA and RA-ILD patients. Of 293 individuals with RA and clinically indicated CT studies, interstitial changes were observed in 22 % (64 of 293; older male smokers), one half of whom had a respiratory complaint at the time of imaging.…”
Section: Implication Of Ila In Ctd: Radiologic Perspectivementioning
confidence: 99%
“…The data of Kawano et al [9] are consistent with those previously reported in literature regarding the prevalence of ILA/ILD in RA [11][12][13][14], such as the baseline demographic characteristics (male sex, older age and smoking history) associated with ILA/ILD [8,12,15,16].…”
Section: Commentarysupporting
confidence: 88%
“…K awano et al [ 9 ] undertook a monocentric, retrospective, observational cohort study. All the adult subjects with a diagnosis of RA, made according to international consensus, seen at the rheumatology clinic from 2014 to 2016 who underwent a chest computed tomography (CT) scan as part of their clinical evaluation entered the study.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations